PERILAKU INVESTASI ANAK PADA KELUARGA MISKIN DAN TIDAK MISKIN - Bahri, Nofia Mutiara; Hartoyo, Hartoyo (Jurnal Ilmu Keluarga dan Konsumen, 2013)
Investment behavior is an important factor to reach qualified children outcomes. This study aimed to analyze the differences in value of children, the investment behaviors, and family expenditure allocation to investment between the children of poor and non-poor families. In addition, this study also aims to analyze the influence of family characteristics, the value of the child, and investment behavior towards children investment expenditure allocation. The study involved 55 families with elementary school children (grade 1 and 2) in Kotabatu village,Ciomas subdistrict, Bogor District, West Java Province. Data were collected by interviewing the mothers and using questionnaire. Data were analyzed using independent samples t-test and multiple linear regression. The results showed that value of children and children’s investment behavior of poor and nonpoor families differ significantly (p<0.01). Parent’s perceptions of economic value had significant negative effect on the expenditures allocation for children’s investment. The expenditures allocation for children’s investment increased with the growing number of schooled children.